1978
DOI: 10.1083/jcb.79.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar membrane agglutination and sexual signaling in the conditional GAM-1 mutant of Chlamydomonas.

Abstract: The temperature-sensitive gametogenesis-defective mutant, gain-1 is sex-limited, expressed only in mating type minus (rot-), and can sexually agglutinate but not fuse at the restrictive temperature (35~ with gametes of wild type (wt) mt +.Thin-section, freeze-cleave, and scanning electron microscopy reveal that the gain-1 phenotype is dependent on both the temperature at which the cells undergo nitrogen starvation (and therefore gamete formation) and the temperature at which the cells are maintained during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Wild-type strains C. reinhardtii CC-620 (rat +) and CC-621 (rot-) and the mutants imp-I rat + (CC-462) (10,12) and gain-1 (CC-1693) (8) were used, as well as C. smithii mt + (CC-13'73) (2), all available from the Chlamydomonas Genetics Center, Duke University, Durham, NC. Plate gametes (19) were suspended in nitrogen-free high-salt minimal medium (NFHSM) I (19) for 1-2 h before use.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type strains C. reinhardtii CC-620 (rat +) and CC-621 (rot-) and the mutants imp-I rat + (CC-462) (10,12) and gain-1 (CC-1693) (8) were used, as well as C. smithii mt + (CC-13'73) (2), all available from the Chlamydomonas Genetics Center, Duke University, Durham, NC. Plate gametes (19) were suspended in nitrogen-free high-salt minimal medium (NFHSM) I (19) for 1-2 h before use.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…If C. smithff is first incubated in db-cAMP/IBMX and then mated, however, widespread agglutination is observed, and when the yield of chloroform-resistant zygotes (17) is analyzed, the treated gametes generate 100 times more zygotes than the controls. A second example is the mutant strain gam-1 mt-which, when allowed to differentiate into gametes in liquid medium at 35°C, usually agglutinates poorly and hence fails to either transmit or receive sexual signals (8). If such gametes are incubated in db-cAMP/IBMX at 35°C for 20 min, their adhesivity improves markedly and they agglutinate with plus gametes as avidly as wild-type minus controls.…”
Section: Agglutinin Recruitment In "Reluctant Maters"mentioning
confidence: 99%
“…Some are directly linked to the mt locus itself (l0, 20), so that certain genes will be found exclusively in mt + but not mt cells, and vice-versa. Others are carried by both haploid mating types but are limited in their expression to one or the other type (5,6,11,14); thus, for example, the "sex-limited" sag-1 locus (11) functions to specify plus flagellar agglutinability in haploid mt + cells, but is apparently not expressed in haploid mt cells. Because the haploid imp-11 mutant derives from wt -and can readily revert to wt -, we can assume that it carries an mt but not an mt + locus and can write its genotype as imp-11 mt -.…”
Section: The Imp-11 Mutationmentioning
confidence: 99%
“…Freeze-fracture electron microscopy has demonstrated that during activation of mt-mating structures, intramembrane particles (IMPs) migrate into the center of the mating structure [22]. It has been postulated that these particles may be involved in fusion between gametes [6,221. Results from other systems also suggest that IMPS may be involved in the fusion process; particle rosettes are seen prior to fusion of: (a) mucocysts and the plasma membrane in Tetrahymena [ 171; (b) trichocysts and the plasma membrane in Paramecium [2]; (c) pinocytotic vesicles in smooth muscle cells [ 121; and (d) the "particle-free area surrounded by membrane particles" that is seen in sperm acrosomes [21].…”
mentioning
confidence: 99%
“…In order to clarify the role of the mt-mating structure particles, it would be useful to determine if any differences are manifested in the mating structures of fusion-defective mutants at the ultrastructural level, during the activation process. Therefore, in these studies we examine freeze-fracture replicas of wild type mt-and 3 conditional fusion-defective mutants [4, 7, 81, (all fusion-defective mutants so far produced have been sexlimited mutants expressed only in mt- [6]) and detail the differences found. A preliminary account of some of these results has previously appeared [Forest, C. L. & Ojakian, G. K. 1986.…”
mentioning
confidence: 99%